2020
DOI: 10.4067/s0718-221x2020005000305
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional stability and colour responses of Pinus elliottii wood subjected to furfurylation treatments

Abstract: Projeto acadêmico sem fins lucrativos desenvolvido no âmbito da iniciativa Acesso Aberto Caracterização da cor da madeira de clones...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…The treatments also induced an increase in both C and hº for both woods, except the hº of the pine wood, which remained approximately unaffected. This indicates that the treated woods presented more homogeneous colour patterns compared to the untreated ones (Acosta et al, 2020c). 3.6.…”
Section: Colour Changesmentioning
confidence: 87%
See 2 more Smart Citations
“…The treatments also induced an increase in both C and hº for both woods, except the hº of the pine wood, which remained approximately unaffected. This indicates that the treated woods presented more homogeneous colour patterns compared to the untreated ones (Acosta et al, 2020c). 3.6.…”
Section: Colour Changesmentioning
confidence: 87%
“…This is attributed to a change in the moisture desorption/absorption mechanisms since no macromolecules from the wood are degraded in this temperature range. Recent studies also reported an increase in thermal stability of wood parts treated by in situ polymerization (Acosta et al, 2020c;Xie et al, 2013).…”
Section: Thermal Decompositionmentioning
confidence: 93%
See 1 more Smart Citation
“…The infrared spectra of modified poplar veneers with different FA solutions and the control group were shown in Figure 7, and the characteristic peak assignments were Compared with the control group, the FA-modified veneer with CA as the catalyst improved the distortion of the cell wall, but the effect was not ideal (Figure 6f). Although part of the wood fiber lumens was filled, more cracks appeared in the intercellular layer, which can be explained by that using CA produced a more hydrophobic FA solution [43]. Therefore, FA molecules cannot fill the pores in the cellular structure.…”
Section: Ftir Analysismentioning
confidence: 99%
“…On the other hand, pine woods have low natural durability and low mechanical performance, especially those woods planted in tropical countries, like Brazil (Acosta et al 2020b). These woods are susceptible to be degraded by both biotic (including fungi, insects, and termites) and abiotic (like ultraviolet radiation, rain, and humidity) agents, which restrict their useful life (Aydemir et al 2016).…”
Section: Introductionmentioning
confidence: 99%